DIMENSIONS OF LEARNERS’ SATISFACTION IN THE DELIVERY OF INSTRUCTION IN BLENDED LEARNING PROGRAM IN TEACHER EDUCATION INSTITUTIONS - Panes, Leah Luisa D (PEOPLE: International Journal of Social Sciences, 2019)
This study sought to explore the levels of satisfaction of learners and the delivery of instruction in teacher education institutions (TEIs) in the Philippinesas seen in the HELAM Model proposed by Ozkan and Koseler. Descriptive exploratory methods involving the collection of quantitative data through an adopted questionnaire for e-learning and qualitative data through interviews and focused group discussions were used. The questionnaire was administered to 358 respondents to gather data on learners’ profileand levels of satisfaction in the delivery of blended learning programs. Statistical analyses revealed no significant difference in the levels of satisfaction and learners’ profiles in terms of gender while significant difference was seen when compared with ICT literacy on computer experience. No significant relationship was seen in the various dimensions affecting the level of satisfaction and the delivery of instruction. Qualitative results emphasized availability of fast and reliable connectivity as the primary concern that affects learners’ satisfaction. Findings suggest that learners in TEIs are highly satisfied with the use of the blended learning program. These results indicate that blended learning may provide transformative potentials in the delivery of instruction just as in the traditional face-to-face environment. Likewise, the study also emphasized the importance of carefully re-designed learning environments considering the various dimensions to achieve satisfied learners that may redound into better quality of education.